Physical activity in stroke patients: A scoping review - Ariyati Amin; Rosyidah Arafat; Rini Rachmawaty (Journal of Community Empowerment for Health, 2021)
Stroke is the second leading cause of disability and death worldwide with 5.9 million deaths annually. Stroke can be followed by various clinical problems. Impaired motoric function of the extremities is the most severe post stroke disorder experienced and impacts on limitations of daily activities. The main treatment is by doing regular physical activity exercises. This review was conducted to identify physical activities that can be performed by stroke patients. This scoping review was compiled using Arksey and O'Malley's five-stage framework. A total of three databases (i.e., Pubmed, Proquest, and DOAJ) was searched with relevant keyword "physical activity OR exercise AND stroke". The articles selected are published in the last 5 years, in English, and in full text. The literature search retrieved 164 studies to be screened based on the exclusion-inclusion criteria which finally resulted in the 11 studies included in the review. The remaining 11 studies were fully read and data were extracted regarding the type of physical activity, goals, settings and outcomes. Qualitative (i.e., theme analysis) methods have been used to synthesis the data. Based on the results of the review, there are several physical activities that stroke patients can do, such as progressive resistance and balance (PRB) exercises, locomotors exercises: (walking on a treadmill with body weight support and walking on the ground), selective movements of the upper and lower trunk body in the Supine and sit using a stable support / pad or unstable support (Swiss ball), core stability training, aerobic (AT) and resistance training (RT), aerobic training, walking exercises, and task-oriented training. Several physical exercises have been identified where each of these exercises has a purpose and benefit in the recovery of physical functional stroke patients. Physical activity should be done regularly and take into account the duration, intensity, and frequency of the exercise based on patient’s ability and stamina.